Multi-jump resonance systems. Issue 2 (1st February 2020) - Buscarino, Arturo; Famoso, Carlo; Fortuna, Luigi; Frasca, Mattia
ABSTRACT: Multi-jump resonance indicates the behaviour of a nonlinear, non-autonomous system whose frequency response is characterised by several hysteresis regions. This paper faces the problem of the design of a nonlinear dynamical system such that it exhibits multi-jump resonance. Analytic aspects of the problem as well as electronic implementation issues of multi-jump resonance circuits are discussed, providing criteria for the design of systems with given hysteresis regions and guidelines for circuit realisation.